Água e espaços transfronteiriços na América do Sul:: questões a partir do território - Rio, Gisela A. Pires do; Drummond, Helena (Sustainability in Debate, 2013)
Many countries remain reticent to the introduction of new institutions and arenas of negotiation in transboundary spaces. Admitting the existence of a peculiar transboundary dynamics, this article presents and discusses issues on water management in transboundary spaces, in order to foment the debates on actual cooperation/conflict situations in South America. We assume that a turbulence of scales is characteristic in these areas. This turbulence of scales is the possibility of the manifestation of cooperation, tensions, conflicts and disputes in multiple scales. The parameters to reflect upon South American reality were defined using examples recently discussed in geographic literature in different regions of the world. These parameters refer to manifestations of agreement and disagreement in the implementation of water management devices through hydrographic basins. In addition to the literature review, documents from international organisms were analyzed in order to identify situations that are projected in various geographical scales. The analysis is focused on raising particular issues to the South American context, offering an agenda for research. In the final section we present the challenges that seem to be more significant to the construction of institutional proximity in transboundary spaces.